2018
DOI: 10.1111/apa.14316
|View full text |Cite
|
Sign up to set email alerts
|

Identification of risk for neonatal haemolysis

Abstract: The combined use of TB/TcB percentile risk assessments and ETCOc measurements can identify infants with haemolytic hyperbilirubinaemia. The addition of TB ROR can identify those infants with elimination disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 20 publications
0
11
0
1
Order By: Relevance
“…Because of this stoichiometry, the rate of CO production (or excretion) as measured as COHb (680,681), total body CO excretion (VeCO) (626), or end-tidal breath CO (ETCO) (617) can serve as an index of the rate of bilirubin production. Several studies have shown that COHb and ETCO, when corrected for inhaled CO, and VeCO levels correlate well in preterm and term neonates and have been used to identify those infants with increased rates of bilirubin production, particularly those undergoing hemolysis (77,627). In the first week of life or 'transitional period', bilirubin production rates in newborns are increased due to a high turnover of RBCs (629,682).…”
Section: A Heme Catabolism and Its Regulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of this stoichiometry, the rate of CO production (or excretion) as measured as COHb (680,681), total body CO excretion (VeCO) (626), or end-tidal breath CO (ETCO) (617) can serve as an index of the rate of bilirubin production. Several studies have shown that COHb and ETCO, when corrected for inhaled CO, and VeCO levels correlate well in preterm and term neonates and have been used to identify those infants with increased rates of bilirubin production, particularly those undergoing hemolysis (77,627). In the first week of life or 'transitional period', bilirubin production rates in newborns are increased due to a high turnover of RBCs (629,682).…”
Section: A Heme Catabolism and Its Regulationmentioning
confidence: 99%
“…Bilirubin production decreases; whereas bilirubin elimination increases as a function of postnatal age in days. Thus, a deviation in this normal pattern of transitional hyperbilirubinemia reflects the likelihood of developing significant hyperbilirubinemia as defined by the Bhutani hour-specific bilirubin nomogram (TSB > 95 th percentile prior to age days) (76,77). By using this nomogram, an infant's hour-specific TSB level can be categorized into defined risk zones (low, lowintermediate, high-intermediate, or high) based on percentiles in order to guide interventions and follow-up.…”
Section: B the Effect Of Hemolysismentioning
confidence: 99%
See 1 more Smart Citation
“…FDA-approved point-of-care noninvasive monitors can quantify the end-tidal CO of neonates. Our recent work, and that of others, has shown that measuring ET-COc during newborn hospitalization can identify hemolysis [19][20][21]. In our new management program, we will obtain an ETCOc on all neonates who meet the phototherapy initiation criteria.…”
Section: Etcoc Measurement For Those Receiving Phototherapy To Determmentioning
confidence: 99%
“…La medición de la BTc se ha utilizado asociada con la Bs junto con la medición del monóxido de carbono al final de la respiración (ETCO, por sus siglas en inglés), permitió identificar a los pacientes con (12) hemolisis en forma precoz .…”
unclassified